A New Battle for History in the Twenty-First Century?. Issue 2 (June 2015) - Trivellato, Francesca
Abstract: This article engages with some of the questions raised by David Armitage and Jo Guldi's "The Return of the longue durée : An Anglo-American Perspective" and their resonance among readers of the Annales . In particular, it challenges the authors' classification of a variety of different historical studies of short periods of time under the rubric of "microhistory." It also questions their argument that such studies are evidence of a "moral crisis" that supposedly dominated anglophone historiography from the cultural revolution of 1968 to the global financial crisis of 2008. Furthermore, the article contrasts the less conventional meanings that Fernand Braudel originally attributed to the longue durée with the ways that Armitage and Guldi interpret this expression. Finally, it asks how, in practice, historians are supposed to follow the authors' invitation to move beyond specialized training and knowledge to produce sweeping new and original interpretations of millennia of human history.